Influence of blood autologous mononuclear on regenerative processes at stromal corneal damages to experiment - N. A. Levchenko; O. I. Krivosheina (Бюллетень сибирской медицины)
In experiment in vivo laws of regeneration of damages of a cornea on background intrastromal introductions of autologus mononuclear blood are studied. It is proved, that local application of mononuclear cells significantly reduces the duration and expressiveness of inflammatory process and as consequence, is accelerated process of regeneration of the damaged corneal tissue.